The influence of printing substrate on macro non-uniformity and line reproduction quality of imprints printed with electrophotographic process - Vujčić, Đorđe; Ružičić, Branka (Journal of Graphic Engineering and Design, 2016)
Print quality is very important for every printing technique. It depends on many different quality attributes. This research included analysis of macro non-uniformities and line reproduction. 16 different paper substrates printed by electrophotographic process were analyzed. They were separated in two groups: coated and uncoated papers. Analysis of macro non-uniformity showed that print mottle has lower values when printed on coated papers than on uncoated papers. Line reproduction analysis showed that the toner spreaded, during melting and fixation, on line edges for both types of paper. According to these results it can be concluded that paper substrate affects the macro non-uniformity and line reproduction, thus overall print quality.